Appendiceal Mixed Adeno-Neuroendocrine Carcinoma: A Population-Based Study of the Surveillance, Epidemiology, and End Results Registry - Brathwaite, Shayna; Yearsley, Martha M.; Bekaii-Saab, Tanios; Wei, Lai; Schmidt, Carl R.; Dillhoff, Mary E.; Frankel, Wendy L.; Hays, John L.; Wu, Christina; Abdel-Misih, Sherif (Frontiers in Oncology, 2016)
Introduction Mixed adeno-neuroendocrine carcinoma (MANEC) is a rare pathological diagnosis recently defined by the World Health Organization (WHO) in 2010. Prior to the definition by the WHO, tumors with both adenocarcinoma and neuroendocrine components were given multiple pathological designations making it difficult to characterize the disease. The aim of our study is to better characterize MANEC to better understand its natural history to influence patient care and positively impact outcomes. Materials and methods The surveillance, epidemiology, and end results program database was queried for all patients aged 18 years or older between 1973 and 2012 who had the diagnosis composite carcinoid (n = 249) of the appendix. Composite carcinoid tumors refer to tumors that have both adenocarcinoma and carcinoid tumor components present, consistent with that pathological diagnosis MANEC. For comparison, the database was also queried for carcinoid tumor of the appendix (n = 950), signet ring cell carcinoma of the appendix (n = 579), and goblet cell carcinoid (GCC) tumors of the appendix (n = 944). The data were retrospectively reviewed, and clinicopathological characteristics, treatment regimens, and survival data were obtained. Results The median age of diagnosis of MANEC tumors was 58 years of age. Eighty percent of patients were White, and 49% were female. Fifty-four percent of patients underwent hemicolectomy and 31% had partial/subtotal colectomy as their surgical management. Median overall survival for MANEC was 6.5 years (95% CI 4.5–9.7), which was statistically significantly shorter (p < 0.0001) in comparison to 13.8 years (95% CI 12.1–16.5) for GCC, 2.1 years (95% CI 1.8–2.3) for signet ring cell carcinoma, and 39.4 years (95% CI 37.1–NA) for carcinoid tumors. Discussion MANEC is a more aggressive clinical entity than both GCC of the appendix and carcinoid tumors of the appendix. Based on these findings, patients with MANEC tumors should undergo aggressive multidisciplinary cancer management.